Pentingnya Pancasila Sebagai Ideologi Negara Dalam Membangun Kesejahteraan Bangsa (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The formulation of Pancasila is contained in the Preamble to the 1945 Constitution. Pancasila has officially become the basis of the state, the state ideology, and is a source of law in statutory regulations. As a state ideology, the values of Pancasila principles must be instilled in the nation from an early age. This is important to preserve culture and maintain the integrity of the Republic of Indonesia from threats from state ideology. Education about Pancasila is an example and way to instill moral and broad-minded individuals in the life of the nation and state. With the erosion of Pancasila values in people's lives, it triggers the threat of loss of national character and other forms of threats such as threats from within the country and from abroad which of course can be detrimental to the people of the nation and state. Threats can be physical or non-physical threats that can occur at any time and can attack anyone. Therefore, it is important for the Indonesian people to explore the nation's ideology, namely Pancasila, and make it a guideline for national life in order to advance general welfare.